Enhanced cryoprecipitate for skin graft and donor site wound healing in pigs. Issue 2 (21st August 2012) - Vetter, Thomas Sebastian; Mowlds, Donald S; Scholz, Thomas; Nam, Su Bong; Lin, Fritz; Owens, John W; Dey, Dilip; Wirth, Garrett A; Evans, Gregory RD
<x xml:space="preserve">Abstract</x> Due to similarities in skin characteristics, the authors hypothesise that a pig model would most accurately show the ability of autologous, enhanced cryoprecipitate (eCryo) to improve the wound healing of split‐thickness skin grafts (STSGs) and corresponding donor sites. Fifty‐two STSGs (5 × 5 cm) were fashioned and treated according to a randomised protocol with an autologous eCryo‐treated and a control group. Macroscopic assessment, histological evaluation and cellular composition were completed at days 7, 14, 21 and 28. Thirty‐two donor sites were also created and assessed in a similar manner. Histologic analysis showed enhancement of healing over all time points for eCryo‐treated donor sites. All other results showed no statistically significant improvement with the use of eCryo. Autologous cryoprecipitate appears to be a safe, inexpensive and easy‐to‐use alternative to fibrin glue, which carries risks and is, in many cases, prohibitively expensive. Further studies are necessary to evaluate the full potential of eCryo. Interestingly, eCryo application may improve donor site aesthetic appearance. We believe that a pig model most reliably simulates eCryo's behaviour in humans to accurately reflect its future clinical applicability.